IDENTIFIKASI PENILAIAN KINERJA KEUANGAN DAN KESEHATAN BANK PERKREDITAN RAKYAT (BPR) DI SURABAYA BERDASARKAN NERACA TRIWULAN DESEMBER 2010 DAN DESEMBER 2011 - KUSUMA DEVI, FITRIYAH Kusuma (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this paper is to assess the performance of BPR in Surabaya in the periodDecember 2010 and December 2011 was assessed through financial ratios represented bythe Reserve Requirement (RR), ROA, and DER. RR which in general has increased, as seenfrom the Rural